Literature Review: Kinerja Guru Sebagai Sumber Daya Manusia Yang Strategis Dalam Sistem Pendidikan di Indonesia - Hesti Kusumaningrum; Hamnah Rofiqoh; Muhammad Asshidiqie Muslich Sumadi; Fitra Syaiful Zidan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Teachers are a key element in the education system, especially in schools. All other components, ranging from curriculum, infrastructure, costs, and so on will not mean much if teachers who hold strategic positions are unable to maximize their performance. The purpose of the literature review is to review how teachers perform as strategic human resources in the education system in Indonesia. Methods: The literature review was conducted based on issues, methodology, similarities and further research proposals. The 5 studies used were qualitative research methods. The results of the 5 studies showed that teacher performance as a strategic human resource in the Indonesian education system is strongly influenced by work motivation factors.